Analisis Beban Kerja Mental Karyawan Perkebunan Kelapa Sawit menggunakan Subjective Workload Assessment Technique (SWAT) and Work Sampling - Safutra, Nur Ihwan; Ahmad, Arfandi (Universitas Al Azhar Indonesia, 2024)
PT. Kurnia Luwuk Sejati or PMKS Toili is one of the palm oil industries that processes fresh fruit bunches into Crude Palm Oil and Palm Kernel Oil. Due to high market demand, palm oil plantation workers are required to complete their tasks on time with a target of 8 working hours per day. Several workers have complained about the physically and mentally burdensome nature of their work, leading to harvest results that sometimes do not meet the desired quality standards. This research aims to determine the level of mental workload experienced by the workers using the SWAT and Work Sampling methods processed using the DosBox 0.74 application. The measurement results can indicate the extent of mental workload perceived by the employees, with three significant factors influencing the employees' mental workload: the time dimension accountsfor 67.16%, the effort dimension accountsfor 13.87%, and the stress dimension accounts for 18.97%. Recommendations for improvement need to be implemented to minimize and reduce the employees' workload, including improving working conditions and the work environment, increasing rest time, effectively distributing tasks, and increasing the number of operators or employees to achieve production targets.Keywords – Mental Workload, SWAT, Work Sampling